2021
DOI: 10.3390/solids2020012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ((La0.60Sr0.40)0.95Co0.20Fe0.80O3-x)-Ag Composite Anode for Direct Ammonia Solid Oxide Fuel Cells and Effect of Pd Impregnation on the Electrochemical Performance

Abstract: Ammonia produced using renewable hydrogen is being viewed as a promising media for the export of energy from locations rich in renewable energy sources. Solid oxide fuel cells (SOFCs) are efficient devices for converting such exported ammonia back into electricity at the point of use; however, investigations on materials and operating regimes for direct ammonia fuelled SOFCs are limited. In this work, we evaluated the direct ammonia SOFC performance with a Silver-Lanthanum Strontium Cobalt Ferrite (Ag-LSCF) co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Our group also recently reported the feasibility of a DASOFC for power generation employing a 3YSZ electrolyte-supported Pd-Ag-LSCF symmetric cell and achieved a power density of 73 mW cm −2 at 800 °C with ammonia fuel. 23 The low power density is due to poor electrolyte-supported cell structure, such as the thick 3YSZ electrolyte (∼300 μm), and the lower catalysis activity of the electrode materials. Recently, Cavazzani et al 85 posed to Pr 2 O 3 nanoparticles and Pr 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3−δ , accompanied by the exsolution of CoFeRu-based alloy nanoparticles that improved the catalytic activity, anti-sintering capability, and stability of the anode.…”
Section: Perovskite Anodesmentioning
confidence: 99%
See 4 more Smart Citations
“…Our group also recently reported the feasibility of a DASOFC for power generation employing a 3YSZ electrolyte-supported Pd-Ag-LSCF symmetric cell and achieved a power density of 73 mW cm −2 at 800 °C with ammonia fuel. 23 The low power density is due to poor electrolyte-supported cell structure, such as the thick 3YSZ electrolyte (∼300 μm), and the lower catalysis activity of the electrode materials. Recently, Cavazzani et al 85 posed to Pr 2 O 3 nanoparticles and Pr 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3−δ , accompanied by the exsolution of CoFeRu-based alloy nanoparticles that improved the catalytic activity, anti-sintering capability, and stability of the anode.…”
Section: Perovskite Anodesmentioning
confidence: 99%
“…Over the past few years, perovskites, double perovskites, spinel oxides, and pyrochlore oxides have also been widely studied as prospective DASOFC anode materials. Rathore et al 84 evaluated a Pd nanoparticle-infiltrated Ag-LSCF composite anode at 800 °C and reported a 43% performance improvement compared with bare Ag-LSCF. The authors concluded that Pd nanoparticles in the anode provided hydrogen dissolution that shifted the ammonia decomposition reaction forward, thus improving the overall cell kinetics.…”
Section: State-of-the-art and Newly Emerging Anode Materials For Dasofcsmentioning
confidence: 99%
See 3 more Smart Citations